Seroprevalence of Rift Valley fever and associated risk factors in livestock of Afar Region, northeastern Ethiopia - Jemberu A. Megenas; Mengistu L. Dadi; Tesfu K. Mekonnen; James W. Larrick; Gezahegne M. Kassa (Current Research in Parasitology and Vector-Borne Diseases)
Rift Valley fever (RVF) is one of the emerging arthropod-borne zoonotic viral diseases with serious public and economic significance in the livestock and human populations of East Africa. Its epidemiology is inadequately recognized in Ethiopia. A cross-sectional study was conducted to investigate the seroprevalence and potential risk factors of RVF in domestic livestock of Amibara and Haruka districts of the Afar Region, northeastern Ethiopia. A total of 736 (224 cattle, 121 goats, 144 sheep, 155 camels and 92 donkeys) blood samples were collected, and serum extracted and tested using competitive ELISA. A questionnaire survey was used to assess potential risk factors of RVF infection. The overall seroprevalence was 22.0% (162/736; 95% CI: 19.41–24.79%). The seroprevalence was significantly higher in goats (42.2%, 95% CI: 39.61–44.99%) compared to that of cattle (14.3%, 95% CI: 11.74–17.09%), sheep (21.5%, 95% CI: 18.91–24.29%), or camels (30.97%, 95% CI: 28.38–33.76%) (P < 0.001). The study showed that seropositivity for IgG antibody to RVFV infection was associated with locality and species of animal. Goats were two times more likely to be seropositive for RVFV infection than cattle (OR: 2.3, 95% CI: 1.462–3.574, P = 0.001). Livestock in the Kealatburi area were five times more likely to be seropositive for RVFV infection than those in the Halidegei area (OR: 5.074, 95% CI: 3.066–8.396, P = 0.001). This study revealed that RVF is an important animal health problem in the Afar Region. Therefore, monitoring of RVF in animals, humans, and vectors along with community sensitization of high-risk populations could benefit mitigating the risk posed by the disease. Quarantine measures should be implemented to reduce the risk of RVFV introduction and dissemination among susceptible animals and ultimately transmission to humans.